A Lithography-Free Fabrication of Low-Operating Voltage-Driven, Very Large Channel Length Graphene Field-Effect Transistor with NH3Sensing Application - Chourasia, N.K.; Singh, A.K.; Rai, S.; Sharma, A.; Chakrabarti, P.; Srivastava, A.; Pal, B.N. (Institute of Electrical and Electronics Engineers Inc., 2020)
Large-area-based field-effect transistor (FET) gas sensor has the potential to provide a larger sensing area for a chemical analyte. So far, graphene FETs (GFETs) are mostly fabricated by expensive lithographic techniques with a minimum channel length. We have demonstrated a simple way to fabricate a very large channel length of 0.45 mm GFET using ion-conducting dielectric with thermally evaporate source/drain electrodes and has been demonstrated for an application of ambient atmosphere ammonia gas sensing. Ion-conducting Li5AlO4 gate dielectric has reduced operating voltage up to 2.0 V with good current saturation. The chemical vapor deposition (CVD) grown uniform monolayer of graphene has been used as an active channel layer of FET. The fabricated device has been tested for different concentrations of ammonia in ambient environment conditions at 25 °C temperature, which indicates that the Dirac point voltage of the device varies up to 0.8 V when the concentration of ammonia has been changed from 0 to 3 ppm. Moreover, this study also reveals that this GFET is capable of detecting ammonia up to the concentration level of 0.1 ppm. © 1963-2012 IEEE.
Keywords: Ammonia sensor; field-effect transistor (FET); graphene; large channel length